(untitled) (Praxis Educativa, 2026)
This paper analyzes the social representations of reading and writing among students of the Faculty of Philosophy and Letters of the Autonomous University of Tlaxcala, Mexico. The objective is to identify variations between profiles, first-year students, intermediate semester students and final semester students. To this end, a survey was applied to 193 participants and qualitative content, factorial and descriptive analyses were carried out. The results show coincidences when considering the comprehension of texts and the expression of ideas as fundamental axes of both practices. However, there is an evolution towards more complex conceptions of reading, linked to an active role as readers and a greater awareness of the communicative purposes of written genres, both school and academic. In this way, it is highlighted that writing is no longer understood only as a means of personal expression and is also recognized by its relationship with the contexts of textual production and circulation.